Desempenho da tilápia-do-Nilo arraçoada com dietas contendo farinha de sangue bovino atomizado ou convencional - Narváez-solarte, Willian Vicente; Pezzato, Antonio Celso [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP]; Polycarpo, Gustavo Do Valle [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2011)
The study evaluated the performance and carcass composition index of Nile tilapia (Oreochromis niloticus) fed with diets containing increasing levels of spray-dried blood meal (SDBM) and vat-dried blood meal (VDBM) and formulated based on digestible amino acids. Two hundred and fifty-two fingerlings were distributed in a completely randomized design, in a (2 x 4) + 1 factorial model, two types of blood meal with four levels of each blood meal in the diet, and a control diet (without blood meal), with four replications. The treatments consisted of soybean meal-based control diet, with 34% digestible protein (DP) and 3,200 kcal of digestible energy kg-1 (DE), plus four diets formulated with SDBM and four diets with VDBM, containing 5, 10, 15 and 20% of each meal in feed, maintaining identical DP, DE, phosphorus, calcium, lysine, methionine, threonine and tryptophan levels as those of the control diet. The results show that it is possible to use up to 15% VDBM in diets of Nile tilapia (O. niloticus) between 5 to 150 g of body weight.

Foi avaliado o desempenho e os índices de rendimento da tilápia-do-Nilo (Oreochromis niloticus) alimentada com níveis crescentes de farinha de sangue atomizado (FSA) ou de farinha de sangue convencional (FSC) em dietas formuladas com base em aminoácidos digestíveis. Foram utilizados 252 alevinos, distribuídos num delineamento inteiramente casualizado, em esquema fatorial (2 x 4) + 1, duas classes de farinha de sangue com quatro níveis de inclusão de cada farinha na dieta, e uma dieta-controle, com quatro repetições. Os tratamentos consistiram em uma dieta-controle à base de farelo de soja, contendo 34% de proteína digestível (PD) e 3.200 kcal de energia digestível kg-1 (ED), mais quatro rações formuladas com FSA e quatro rações com FSC, com inclusões de 5, 10, 15 e 20% de cada farinha na ração, mantendo-se os níveis de PD, ED, fósforo, cálcio, lisina, metionina, treonina e triptofano idênticos aos da dieta-controle. Concluiu-se que é possível utilizar até 15% da FSC em rações para tilápia-do-Nilo na fase de 5 a 150 g de peso vivo.
Performance of nile tilapia fed with spray-dried or vat-dries bovine blood meal
Keywords: aminoácidos; desnaturação; proteína; Oreochromis niloticus; amino acids; degradation; protein; Oreochromis niloticus